Alleviation of Zn toxicity by low water availability (Physiologia Plantarum, 2013)
Heavy metal contamination and drought are expected to increase in large areas worldwide. However, their combined effect on plant performance has been scantly analyzed. This study examines the effect of Zn supply at different water availabilities on morpho-physiological traits of Quercus suber L. in order to analyze the combined effects of both stresses. Seedlings were treated with four levels of zinc from 3 to 150 µM and exposed to low watering (LW) or high watering (HW) frequency in hydroponic culture, using a growth chamber. Under both watering regimes, Zn concentration in leaves and roots increased with Zn increment in nutrient solution. Nevertheless, at the highest Zn doses, Zn tissue concentrations were almost twice in HW than in LW seedlings. Functional traits as leaf photosynthetic rate and root hydraulic conductivity, and morphological traits as root length and root biomass decreased significantly in response to Zn supply. Auxin levels increased with Zn concentrations, suggesting the involvement of this phytohormone in the seedling response to this element. LW seedlings exposed to 150 µM Zn showed higher root length and root biomass than HW seedlings exposed to the same Zn dose. Our results suggest that low water availability could mitigate Zn toxicity by limiting internal accumulation. Morphological traits involved in the response to both stresses probably contributed to this response.
APS